PERSEPSI PEMUDA TERHADAP PARTAI POLITIK NASIONALPESERTA PEMILU 2014 DAN IMPLIKASINYA TERHADAPKETAHANAN POLITIK WILAYAH (Studi Pada KNPI Provinsi Banten) - Hermawan, Agus Aan (Jurnal Ketahanan Nasional, 2014)
The perception of young man to political party of participant of general election 2014 that political party had not committed function of political party well as according to its function. The function of the politics party which was not either done that was political communicative function, the function of political socialization or political education, the function of political recruitment, and function of conflict regulator. party mod system which multi party was considered that there were still too much the numbers. Vision and political party mission considered were not consistent with reality programme its activity. The quality of political cadre and party achievement seen that there were still minim in pushing refinement of public life. perception of implication Young man to political resilience of region in Banten affected at legitimation decline government, Government policy was not supported by young man, and political participation of low young man. The increasing of young man opinion at un-believe at law enforcement officer, political system of democracy was seen could not yet push political stability which either due then could be done procedurally did not touch substance of value of democracy. The condition with implication to menaced at political resilience in the region of Bantenâs provinceKeywords: Perceptions of Youth, Political Parties, Political Resilience of Region